THE CONTENT OF A SUCCESSFUL FOREIGN TRADE STRATEGY OF ENTERPRISES IN THE CONDITIONS OF EUROPEAN INTEGRATION PROCESSES - Tkach, O. V. (The actual problems of regional economy development, 2024)
The effectiveness of any country participation in world markets is determined by the activity of its business entities of various ownership forms, their effective strategies for promoting goods to foreign markets and successful foreign economic agreements concluded with trading partners. The article examines the peculiarities of taking into account in the strategy of foreign economic activities of enterprises world rules and norms regarding the principles of conclusion, structure and execution of international contracts in the context of their compliance with international norms and principles of free choice of the nature of agreements and their execution under the conditions of integration processes into the European Community. The main purpose of the publication: presentation of the necessary levers for use by business entities in the preparation, processing and conclusion of foreign economic buy and sale contracts, free choice of location and norms of legal support for foreign economic agreements. A comparative analysis of the application of the principles and norms of the Law of International Treaties Vienna Convention and the international legal system for regulating relations in the field of international trade based on commercial rules and principles (lex mercatoria) is presented when concluding international purchase and sale of goods contracts. In the presented publication, as a conclusion and a scientific novelty, it is proposed to take into account in the strategies of foreign economic activity of enterprises and organizations both the provisions of the Vienna Convention on the Law of International Treaties and the international legal system for regulating relations in the field of international trade based on commercial rules and principles (lex mercatoria). The limitation of interference in foreign economic activity when concluding the purchase and sale of goods international contracts of practical importance, which is determined by the basic principles of the Vienna Convention for regulating relations in the field of international trade based on commercial rules and principles of lex mercatoria, as well and requirements of convergent processes to the European Economic Community.